MSMEs Interest In Technology-Based Financing (Equity Crowdfunding) - Rusnawati; Qamariah (International Journal of Education Management and Religion, 2026)
Indonesia is a country with a high number of Micro, Small and Medium Enterprises (MSMEs) growth and has great potential for development, the development of MSMEs in Indonesia is supported by various government programs whose aim is to increase the quantity and quality of MSMEs in Indonesia. MSMEs are a business line that has a large role and potential in supporting the Indonesian economy and improving people's welfare. MSMEs have a vital role in the Indonesian economy by contributing to the increase in BPD by more than 60% or worth 8,573.89 trillion Rupiah, their ability to absorb a fairly high workforce reaching 97% of the total existing workforce, can collect up to 60.4% of total investment, equal distribution and increase income, to realize a stable, balanced and growing national economic system. This study is a multiple linear regression research that aims to examine the influence of social influence and compatibility on MSMEs’ interest in technology-based equity crowdfunding, using the grand theories of UTAUT and the Diffusion of Innovation (DOI) Theory. This research is associative in nature with a quantitative approach. The type of data used is primary data, collected through survey research by distributing questionnaires to respondents both directly and online. The respondents consisted of 140 MSMEs selected through purposive sampling, with the criteria that the respondents were MSMEs located in Makassar City and had been operating for at least two years. The results of the study reveal that the variables of social influence and compatibility have a positive and significant effect on MSMEs’ interest in technology-based equity crowdfunding.